PENINGKATAN AKTIVITAS BELAJAR DAN PENGUASAAN KONSEP EKOSISTEM MELALUI PEMBELAJARAN KONTEKSTUAL DI SMA TELADAN 1 METRO - Oka, Anak Agung (Bioedukasi Jurnal Pendidikan Biologi, 2010)
This research was intended to 1) know how to increase the studentsâ activity of class X of SMA Teladan 1 Metro through contextual learning based on inquiry 2) know how master the concept about ecosystem of students class X of SMA Teladan 1 Metro through contextual learning based on inquiry 3) know whether there is increase of learning activity and mastery of ecosystem concept through contextual learning based on inquiry. To gain the objectives above, the research method used in this research was Classroom Action Research (PTK). The subject of the research were the students of class X of SMA Teladan 1 Metro. Based on the result of data analysis, it was found that 1) Contextual Learning can increase the student learning activity, which covers: a) listening to teacher explanation activity which was 5-10 % previously out of the whole class became 96%, b) proposing idea activity which was previously 1-5% out of all students became 94%, c) observation activity which was previously 15% out of all students became 85%, d) activity in following discussion which was 15% previously out of the whole students became 84%, e) activity in doing analysis and reporting the result was 10% previously became 96%. 2) Contextual learning can increase concept of ecosystem mastery by comparing pre-test and post test result in the end of the cycle 2. From the analysis, it was found that the Gain score was normalized became 0,793 or there was increase of concept mastery as high as 79.3% from the gain before the treatment compared to after the treatment, and 3) contextual learning can increase learning activity and concept of ecosystem mastery.Â Kata kunci: Contextual Teaching and Learning, Aktivitas Belajar, Penguasaan Konsep